DESIGN AND ANALYSIS OF GO-KART STEERING SYSTEM - PROF. JAGTAP S.T.; PROF. G.R. DRSHPANDE (International Journal of Innovations in Engineering Research and Technology, 2021)
This work include the theory, design and analysis of go-kart Steering system. Usually a go-kart or owner who wants to improve the handling of the vehicle will have to purchase the latest in wheels, tires and other optional equipment, but end up finding that those things in fact handles worse. The first stage in achieving a good handling kart that will provide the greatest percentage of power efficiency is to go right back tobasics.The most conventional steering arrangement is to turn the front wheels using a hand–operatedsteering wheel which is positioned in front of the driver, via the steering column, which may contain universal joints (which may also be part of the collapsible steering column design), to allow it to deviate somewhat from a straight line. From the work steering ratio 3.8376 :1 is achieved, Ackerman angle 13.522 And turning radius of 3.8255m to enhance the steering effect.